Karakteristik Sosis Ikan Lele Dumbo (Clarias gariepinus) dengan Penambahan Bubuk Bunga Rosella (Hibiscus sabdariffa) - Imran Imran; Herpandi Herpandi; Susi Lestari (Jurnal FishtecH, 2016)
The purpose of this research was to investigate the effect of addition rosella powder to characteristics sausage of catfish (Clarias gariepinus) and knowing the best formulation the acceptance of panelists on the antioxsidant activity. This research was used random block design (RBD). The treatment of addition rosella powders were 1%, 2%, 3%, 4%, and 5%. Parameters of this research were physic analysis such as elasticity, colour and pH. Chemical analysis such as water and ash. Sensoric analysis such as display, texture, colour, flavor and taste. The result showed that addition rosella powder gave significant effect on elasticity, lightness, redness, pH, water content and sensoric analysis such as display, texture, colour, flavor and taste, but they were no effect to ash and yellowness. The elasticity of this sausage interval 54.93-153.6 (gf), lightness was 38.66% - 61.96%, redness was 3.8% -7.6%, yellownes was 4.33 -13.43, pH was 4.21 – 6.75. Water content interval 62.03%. – 73.96%, ash was 2.57- 3.3 and display of analysis sensoric was 4.04-7.46, texture was 3.28 – 7.12, flavor was 3.96 – 8.04, colour was 2 – 7.36, and taste was 5.08 – 7.6. Based on the acceptance panelists the best formulation on treatment A2 with addition concentration rosella powder 1 % and antioxidant activity was 11.6 ppm.